nayl al'umnit ealaa muqadimat aleazia Sheikh Muhammad Ali bin Hussein bin Ibrahim al-Makki al-Maliki 1367h- Study and investigation - FOUAD bin Ahmed, Atallah (Milev Journal of Research and Studies, 2020)
This research consist of a study and investigation of the manuscript: (nayl al'umnit ealaa muqadimat aleazia), by Sheikh Muhammad Ali bin Hussein al-Maliki al-Maliki (1367h), in Maliki Fiqh, the researcher saw the importance of publication of the manuscript, because of that he wrote this research, that consists the introduction of the Author and an introduction of the manuscript. overall, the research enhanced on many progressive outcomes that are valuable in the field of this research.